2013
DOI: 10.1007/s00436-013-3526-9
|View full text |Cite
|
Sign up to set email alerts
|

Dirofilaria repens microfilariae in Aedes vexans mosquitoes in Slovakia

Abstract: In this study, we screened field-caught mosquitoes for presence of Dirofilaria spp. by using a polymerase chain reaction (PCR) assay. Potential occurrence of Dirofilaria repens and Dirofilaria immitis microfilariae was examined in 3,600 mosquitoes of eight species (Aedes vexans, Aedes cinereus, Aedes rossicus, Culex pipiens, Culiseta annulata, Ochlerotatus sticticus, Ochlerotatus cantans and Ochlerotatus caspius) collected from five locations in two districts (Kosice and Trebisov) of Eastern Slovakia, endemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…)/ torrentium D. repens and D. immitis Italy [49], Serbia [39]Belarus [16], Italy [40, 46, 49, 58], Serbia [39], Turkey [50], Germany [53], Portugal [41], Hungary [63], Spain [42] Anopheles maculipennis ( s.l . ) D. repens and D. immitis Germany [53, 60], Austria [61], Hungary [38]Italy [40], Portugal [41] Aedes vexans D. repens Czech Republic [62], Germany [60], Hungary [38], Serbia [39], Slovakia [43, 44]Italy [58], Turkey [50] Culex modestus D. repens Hungary [38]Hungary [63] Aedes annulipes D. repens Hungary [38] Culiseta annulata D. repens Germany [60] Aedes caspius D. repens Italy [58], Hungary [63], Portugal [41], Serbia [39] Aedes sticticus D. repens Hungary [38], Serbia [39] Coquillettidia richiardii D. repens Hungary [38]Serbia [39], Italy [40] …”
Section: Discussionmentioning
confidence: 99%
“…)/ torrentium D. repens and D. immitis Italy [49], Serbia [39]Belarus [16], Italy [40, 46, 49, 58], Serbia [39], Turkey [50], Germany [53], Portugal [41], Hungary [63], Spain [42] Anopheles maculipennis ( s.l . ) D. repens and D. immitis Germany [53, 60], Austria [61], Hungary [38]Italy [40], Portugal [41] Aedes vexans D. repens Czech Republic [62], Germany [60], Hungary [38], Serbia [39], Slovakia [43, 44]Italy [58], Turkey [50] Culex modestus D. repens Hungary [38]Hungary [63] Aedes annulipes D. repens Hungary [38] Culiseta annulata D. repens Germany [60] Aedes caspius D. repens Italy [58], Hungary [63], Portugal [41], Serbia [39] Aedes sticticus D. repens Hungary [38], Serbia [39] Coquillettidia richiardii D. repens Hungary [38]Serbia [39], Italy [40] …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, study of Miterpáková et al (2008) in dogs confirmed the existence of highly endemic localities in southern parts of the country with mean prevalence rate of 34.5 %. In south-eastern part of Slovakia the positivity of Aedes vexans mosquitoes, D. repens intermediate hosts, was observed by Bocková et al (2013). Autochthonous cases of human dirofilariosis were also recorded (Hrčková et al 2013;Ondriska et al 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Taking into account the long flying distance (migrations of up to 15 km), this species becomes suitable for local transmission and the spread of zoonotic dirofilariosis into new endemic foci. Outside the traditional Mediterranean distribution area, dirofilarial worms have also recently been described in mosquitoes from Slovakia (Bocková et al 2013), Austria (Silbermayr et al 2014) and Germany (Czaijka et al 2014;Kronefeld et al 2014), the more so as in two of the four cases (Bocková et al 2013;Czajka et al 2014) Ae. vexans was involved.…”
Section: Resultsmentioning
confidence: 97%